Gestión por procesos administrativos y su incidencia en la calidad de servicio en Mega Ferretería Bonilla en el cantón La Maná, provincia de Cotopaxi, año 2018. - Hurtado Quevedo, Marjory Nataly (2019)
The purpose of this research was to analyze the management of administrative processes and its impact on the quality of service at Mega Ferretería Bonilla in the municipality of La Maná, with a proposal for a management model for administrative processes applied to the hardware sector, which emerged as research contribution due to problems arising from quality of service, this leads to dissatisfied customers which cause the volume of sales to decrease, a worrisome situation that causes us to investigate and propose a viable solution. For the development of the proposed objectives the types of research were used: formative to establish the mechanisms to integrate the research process, bibliographic research to elaborate the theoretical foundation, diagnostic investigation to know the problems in the research, correlational research for establish the level of dependence of the variables, field research through the application of interviews, surveys and proactive research for the development of the proposal. The results of the situational diagnosis allowed to know the main problems at the administrative level were deficiencies in the leadership, lack of a post-sale monitoring that allows knowing with certainty the level of satisfaction of its clients, while the surveys directed to the users allowed to establish that the customers showed satisfaction regarding the quality of the products, prices and speed of attention; However, a significant percentage evidenced problems regarding the technical knowledge of the employees of the customer service area and compliance with the delivery time of the product. The contrast made by calculating the chi-square (X2) with a level of significance of 5% reflected that the variable technical knowledge (administrative management) is independent of the home delivery variable and the administration variable of the hardware store is dependent on the After sales follow-up variable in Mega Ferretería Bonilla, emphasizing that administrative management depends on the quality of service, therefore the EFQM process management model was suggested, which included strategies such as: the profile of the leader, policies, strategies of the 5S, promotions, offers, after sales follow-up, training plan on customer service, functions manual; which, when applied, will improve the quality of the service significantly in Mega Ferretería Bonilla.